The Influence of Paylater Usage in E-Commerce on Impulsive Buying of Fashion Products - Putri Anastasya Vernanda; Esty Nurbaity Arrsyi; Suryawati (Universitas Negeri Semarang, 2025)
This research aims to determine the influence of paylater usage in e-commerce on impulsive buying of fashion products. This research uses a survey method with a quantitative approach. The sample for this research was 120 with sampling using accidental sampling technique. The data analysis technique used is the chi square test. The results of data analysis show that there is no influence between the use of the payLater payment system in e-commerce and impulsive buying of fashion products. From the results of this research, it can be concluded that consumer behavior tends to be impulsive in purchasing fashion products on e-commerce, whether using paylater or not using paylater.